2021
DOI: 10.1515/tnsci-2020-0167
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulation and antidepressant effect of ketamine

Abstract: Major depressive disorder (MDD) is a common mental health disorder that brings severe disease burden worldwide. Traditional antidepressants are mainly targeted at monoamine neurotransmitters, with low remission rates and high recurrence rates. Ketamine is a noncompetitive glutamate N-methyl-d-aspartate receptor (NMDAR) antagonist, and its rapid and powerful antidepressant effects have come to light. Its antidepressant mechanism is still unclarified. Research found that ketamine had not only antagonistic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 107 publications
0
10
0
Order By: Relevance
“…The activation of the immune system is associated with depression and the anti-inflammatory effect of antidepressant treatment is related to response [ 75 ]. A recent meta-analysis revealed that antidepressant treatment was related to a significant TNF-α decrease in responders [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The activation of the immune system is associated with depression and the anti-inflammatory effect of antidepressant treatment is related to response [ 75 ]. A recent meta-analysis revealed that antidepressant treatment was related to a significant TNF-α decrease in responders [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the immunoregulatory effects of esketamine may interact with the affected and closely linked immune and nervous system in CPRS patients [ 7 , 50 ]. For instance, recent studies on depression and comorbid pain described the immunoregulatory aspects of esketamine that may result in downregulation of peripheral pro-inflammatory cytokines and the attenuation of central glial cells [ 8 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies, ketamine exerts its antidepressant effects by modulating the immune system, including peripheral inflammatory cytokines, central microglia, and astrocytes. 44 Furthermore, the GO enrichment analysis of 113 mRNAs in the ceRNA network unveiled a predominant involvement of these mRNAs in biological processes associated with drug transport. Drug transport is the kinetic process of the absorption, distribution, metabolism and excretion of drugs from the body.…”
Section: Discussionmentioning
confidence: 99%